Influence of Competitiveness, Corruption and Foreign Direct Investment on Economic Growth of Asean Developing Countries - Afif, Fadeli yusuf; Ciptawaty, Ukhti (FEB - Universitas Lampung, 2020)
The purpose of this study is to look at the condition of the country's competitiveness and its influence on ASEAN economic growth. The data used is panel data consisting of time series data for 2009 - 2019 and cross section of five ASEAN countries with the highest level of competitiveness. The variables used are economic growth, competitiveness, corruption perception index, political risk, and foreign direct investment. The analysis tool used is panel data regression, the Random Effect Model (REM). The results show that competitiveness and foreign direct investment have a positive and significant effect on economic growth, while the corruption perception index has no effect on economic growth in 5 ASEAN countries.